Oral Mucosa Derived α−Synuclein as a Potential Diagnostic Biomarker for Parkinson′s Disease - Zheng, Yuanchu; Yu, Zhenwei; Zhao, Jiajia; Cai, Huihui; Wang, Zhan; Wang, Xuemei; Feng, Tao (Frontiers in Aging Neuroscience, 2022)
Background Pathological α-synuclein (α-Syn) is not only exclusive to the central nervous system (CNS) in Parkinson’s disease (PD), but also extended to biofluids and peripheral tissues including oral cavity. Both oral mucosa and nervous system are derived from ectodermal tissue, and potentially share common disease-specific characteristics. Oral mucosal exfoliative cytology is a non-invasive technique, which is an easily acceptable for patients and ordinary people. The purpose of this study was to determine the abnormal accumulation of α-Syn in oral mucosa of PD patients and to learn the diagnostic utility of oral mucosa α-Syn for PD. Methods The oral mucosa samples were obtained from 57 patients with PD and 51 age-matched controls by cytological brush. Immunofluorescence analysis was used to investigate the presence and subcellular localization of α-Syn, phosphorylated α-Syn at Ser129 (pS129) and oligomeric α-Syn in the oral mucosa cells of PD patients and controls. Images taken as Z-stacks were analyzed for 3D reconstruction to visualize the α-Syn intracellular localization. Then, the concentrations of α-Syn, pS129, and oligomeric α-Syn in oral mucosa samples were measured using electrochemiluminescence assays. Results Immunofluorescence images revealed the increased α-Syn, pS129, and oligomeric α-Syn levels in oral mucosa cells of PD patients than age-matched controls. The intracellular distributions of α-Syn species were determine by Z-stack images with 3D reconstruction, and α-Syn was detected in both the nucleus and cytoplasm. However, pS129 was mainly located in the cytoplasm, and oligomeric α-Syn was highly expressed in the nucleus and perinuclear cytoplasm. The concentrations of three α-Syn species were significantly increased in the oral mucosa cell samples of PD patients than controls (α-Syn, p = 0.001; pS129, p = 0.002; oligomeric α-Syn, p = 0.013). In PD patients, the oral mucosa α-Syn and oligomeric α-Syn levels were significantly correlated with Hoehn-Yahr scales (α-Syn, r = 0.495, p = 0.001; oligomeric α-Syn, r = 0.324, p = 0.03). The area under curve (AUC) of ROC analysis using an integrative model including α-Syn, pS129, and oligomeric α-Syn for PD diagnosis was 0.749, with 66.7% sensitivity and 72.5% specificity. Conclusion This study for the first time demonstrated increased expressions of α-Syn, pS129, and oligomeric α-Syn in oral mucosa cells from PD patients, which serve as useful and non-invasive PD diagnostic biomarkers.